Developing inclusive digital health diagnostic for schistosomiasis: a need for guidance via target product profiles - Onasanya, Adeola; Bengtson, Michel; de Goeje, Ludo; van Engelen, Jo; Diehl, Jan-Carel; van Lieshout, Lisette (Frontiers in Parasitology, 2023)
The INSPIRED project aims to develop inclusive Digital Optical Diagnostic Devices (DODDs) for schistosomiasis, to support disease management by enabling rapid diagnostic results, to improve efficient data management to guide decision-making and to provide healthcare workers with critical health information to facilitate follow-up action. Due to the non-availability of Target Product Profiles (TPPs) for guiding the development of digital diagnostics for schistosomiasis, we explored existing diagnostic TPPs. Using a curated open-access database (Notion database), we studied a selection of TPPs for diagnosing infectious diseases, focusing on specifications related to digital health products for Neglected Tropical Diseases (NTDs). Eighteen TPPs originating from 12 documents, covering 13 specific diseases, were selected and their characteristics were labelled and entered into the database. Further exploration of the database revealed several gaps, including a lack of stakeholder input, sustainability, and TPP availability. Other significant gaps related to digital health platform interconnectivity and data stewardship specifically in relation to digital diagnostics, including DODDs. These findings reflect two possible scenarios: (1) there is currently no need for digital diagnostic devices for schistosomiasis and, by extension for other NTDs; or (2) those needs are not yet covered by TPPs. Therefore, we recommend that digital health diagnostics are included in the use cases for schistosomiasis control and elimination, at least in the ideal/desirable scenario, as this will guide research and incentivize investment in digital health diagnostics for schistosomiasis. 1 Field Code Changed Formatted: Dutch (Netherlands) Formatted: Dutch (Netherlands) Field Code Changed Formatted: English (United States) Field Code Changed Field Code Changed Formatted: English (United States) Field Code Changed Formatted: Dutch (Netherlands) Formatted: Dutch (Netherlands) Field Code Changed Formatted: Dutch (Netherlands) Formatted: Dutch (Netherlands) Field Code Changed Formatted: Dutch (Netherlands) Formatted: Dutch (Netherlands) Field Code Changed Field Code Changed Formatted: Dutch (Netherlands)